Study on the Antimicrobial Properties of Citrate-Based Biodegradable Polymers - Su, Lee-Chun; Xie, Zhiwei; Zhang, Yi; Nguyen, Kytai Truong; Yang, Jian (Frontiers in Bioengineering and Biotechnology, 2014)
Citrate-based polymers possess unique advantages for various biomedical applications since citric acid is a natural metabolism product, which is biocompatible and antimicrobial. In polymer synthesis, citric acid also provides multiple functional groups to control the crosslinking of polymers and active binding sites for further conjugation of biomolecules. Our group recently developed a number of citrate-based polymers for various biomedical applications by taking advantage of their controllable chemical, mechanical, and biological characteristics. In this study, various citric acid derived biodegradable polymers were synthesized and investigated for their physicochemical and antimicrobial properties. Results indicate that citric acid derived polymers reduced bacterial proliferation to different degrees based on their chemical composition. Among the studied polymers, poly(octamethylene citrate) (POC) showed approximately 70-80% suppression to microbe proliferation, owing to its relatively higher ratio of citric acid contents. Crosslinked urethane-doped polyester elastomers (CUPEs) and biodegradable photoluminescent polymers (BPLPs) also exhibited significant bacteria reduction of ~20% and ~50% for Staphylococcus aureus and Escherichia coli, respectively. Thus, the intrinsic antibacterial properties in citrate-based polymers enable them to inhibit bacteria growth without incorporation of antibiotics, silver nanoparticles, and other traditional bacteria-killing agents suggesting that they are unique beneficial materials for wound dressing, tissue engineering, and other potential medical applications where antimicrobial property is desired.